2018
DOI: 10.1101/324939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced inhibition of influenza virus infection by peptide-noble metal nanoparticle conjugates

Abstract: Influenza virus is a major medical and veterinary health concern and causes global pandemics. The peptide 'FluPep' is an established inhibitor of influenza virus infectivity in model systems. We have explored the potential for FluPep functionalised noble metal nanoparticle to enhance the antiviral activity of the peptide Flupep and determined their potential for the delivery of FluPep. The FluPep ligand designed here is FluPep extended at its N-terminus with the sequence CVVVTAAA-, to allow its incorporation i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Emileh et al have reported gold nanoparticle–peptide triazole conjugates to be active against HIV-1 by disrupting the interactions between host receptor proteins and trimeric envelope spike glycoprotein of virus [ 155 ]. Recently, Alghrair et al functionalized silver and gold nanoparticles with an antiviral peptide FluPep and reported increased antiviral potency against influenza A virus [ 156 ].…”
Section: Nanotechnology Formulation Aspects and Their Application In mentioning
confidence: 99%
“…Emileh et al have reported gold nanoparticle–peptide triazole conjugates to be active against HIV-1 by disrupting the interactions between host receptor proteins and trimeric envelope spike glycoprotein of virus [ 155 ]. Recently, Alghrair et al functionalized silver and gold nanoparticles with an antiviral peptide FluPep and reported increased antiviral potency against influenza A virus [ 156 ].…”
Section: Nanotechnology Formulation Aspects and Their Application In mentioning
confidence: 99%
“…Alghrair et al reported that AgNPs and AuNPs functionalized with FluPep, a peptide that can effectively inhibit influenza A viruses (IAVs), showed greater antiviral activity than free FluPep. 94 Haag and co-workers used electron microscopy imaging to visually show that AuNPs functionalized with sialic-acid-terminated glycerol dendrons specifically targeted the viral HA protein to effectively inhibit viral proliferation. 55 Moreover, various NPs, such as oseltamivir-functionalized AgNPs, 63 AgNP/chitosan composites, 95 zanamivir-functionalized AgNPs, 64 zanamivir-functionalized SeNPs (through the p38 and JNK signaling pathways), 67 amantadine-functionalized SeNPs (through the ROS-mediated AKT signaling pathways), 68 ribavirin-functionalized SeNPs (via the caspase-3 apoptotic pathway), 69 oseltamivir-functionalized SeNPs, 70 PEGylated-ZnO NPs, 71 and anionic AuNPs, 56 have also been fabricated and investigated for inhibitory effects on and biocompatibility with H1N1, a current seasonal virus that caused two deadly global pandemics in 1918 and 2009.…”
Section: Nanoparticles For Therapeuticsmentioning
confidence: 99%
“…"FluPep" is an established peptide inhibitor of influenza type-A virus; however, silver and gold peptide (FluPep) NPs were synthesized and tested for enhanced antiviral activity [146]. Silver and gold NPs functionalized with FluPep ligand (0.03%) showed inhibition (50%) against the influenza A virus strain at concentrations of 0.14 nM and 0.073 nM, respectively.…”
Section: Influenzamentioning
confidence: 99%